Analysis of the Implementation Health UU Number 17 of 2023 Article 12 Concerning Improving the Quality of Human Resources in Health Services at RSUD Dr. Hadrianus Sinaga Pangururan - Br.Sembiring, Tamaulina; Pardosi, Manahap Cerarius Fransiskus (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the implementation of Health Law No. 17 of 2023 Article 12 concerning improving the quality of Human Resources (HR) in health services at RSUD Dr. Hadrianus Sinaga Pangururan. The Society 5.0 era emphasizes accelerating human resource development, especially in the health sector, as the key to achieving quality and superior health services. Human resources in hospitals, including nurses, doctors, and other health workers, play an important role in improving service quality and patient satisfaction. This study uses a literature study approach to identify the relevance of Health Law No. 17 of 2023 with the development of health human resources in Indonesia. The results of the analysis show that the implementation of the Law requires extra attention in management, competency development and monitoring the quality of human resources at RSUD Dr. Hadrianus Sinaga Pangururan. The conclusion of this research is the importance of the government in ensuring the fulfillment of consistent health service standards, effective human resource management, and ongoing evaluation of the competence of medical personnel. Recommendations include increasing investment in continuous training to improve HR competency and improving monitoring systems to ensure implementation of Health Law no. 17 of 2023 which was successful at RSUD Dr. Hadrianus Sinaga Pangururan.